2014
DOI: 10.1002/j.1556-6676.2014.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Racial Microaggressions on Mental Health: Counseling Implications for Clients of Color

Abstract: This study examined the relationship between racial microaggressions (subtle and unintentional forms of racial discrimination) and mental health. Results from a large sample (N = 506) indicated that higher frequencies of racial microaggressions negatively predicted participants' mental health and that racial microaggressions were significantly correlated with depressive symptoms and negative affect. Differences in the types of microaggressions experienced by various racial groups (Asian, Latina/o, Black, White… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
313
1
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 387 publications
(358 citation statements)
references
References 35 publications
13
313
1
10
Order By: Relevance
“…We asked White and racially diverse participants to self-report their experience of racial microaggressions and rate the offensiveness of racial themed and non-racial themed (control images) Internet memes. As the first empirical investigation conducted in the United Kingdom, replicating previous research from the United States (Nadal et al, 2014) , we anticipate that People of Color…”
Section: Current Studymentioning
confidence: 93%
See 3 more Smart Citations
“…We asked White and racially diverse participants to self-report their experience of racial microaggressions and rate the offensiveness of racial themed and non-racial themed (control images) Internet memes. As the first empirical investigation conducted in the United Kingdom, replicating previous research from the United States (Nadal et al, 2014) , we anticipate that People of Color…”
Section: Current Studymentioning
confidence: 93%
“…For example, Whites report more difficulty in determining the offensiveness of an ambiguous prejudicial comment as compared to a more overt instance of racial discrimination (Zou & Dickter, 2013). However, People of Color are aware of racial microaggressions; they report experiencing this subtle discrimination frequently across a wide variety of domains (see Wong et al, 2013, for a review) to a greater extent than their White counterparts (Nadal et al, 2014). Due to previous personal experience with racial microaggressions, People of Color may become more sensitive to signs of racial bias and readily attribute these actions to racism (Dovidio et al, 2002).…”
Section: Racial Microaggressions and Perceptions Of Internet Memesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although more recent work has investigated the psychological impact of ethnic microaggressions among Asian Americans (Ong, Burrow, Fuller-Rowell, Ja, & Sue, 2013) and African Americans (Torres, Driscoll, & Burrow, 2010), there remains a lack of studies with Latino samples. Ethnic microaggressions have been associated with mental health problems, particularly depression and lack of positive affect, among a multiethnic sample including Latinos (Nadal, Griffin, Wong, Hamit, & Rasmus, 2014). Huynh (2012) sampled Latino and Asian American adolescents and reported that the experience of microaggressions, in conjunction with the negative reactions to these experiences, was associated with heightened depressive and somatic symptoms.…”
mentioning
confidence: 99%